2021
DOI: 10.1088/1755-1315/886/1/012123
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Trichoderma antagonist saprophytic fungi and its use for biocontrol of Fusarium wilt disease on shallots at Lombok Island, West Nusa Tenggara, Indonesia

Abstract: One of the obstacles in the development of shallots in West Nusa Tenggara (NTB) is the presence of Fusarium wilt disease. The use of antagonistic saprophytic fungi Trichoderma spp. is a biological control technique. The aim of this research is to explore the biodiversity of Trichoderma spp. and its use for controlling Fusarium wilt disease. Research using exploratory methods conducted at the shallot planting center on Lombok Island included isolation of antagonistic saprophytic fungi, purification and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Efficacy value for controlling moler diseases with the treatment of T. harzianum at the planting time is 62.50 (Table 1). The effectiveness of T. harzianum as a biological control agent for moler disease has been shown in the previous studies [12][13][14]. T. harzianum has been widely reported as a biological control agent for plant diseases caused by fungi such as F. oxysporum [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy value for controlling moler diseases with the treatment of T. harzianum at the planting time is 62.50 (Table 1). The effectiveness of T. harzianum as a biological control agent for moler disease has been shown in the previous studies [12][13][14]. T. harzianum has been widely reported as a biological control agent for plant diseases caused by fungi such as F. oxysporum [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…T. harzianum controls F. oxysporum by colonizing the rhizosphere and plundering nutrients [23]. T. harzianum does mycoparasitism by producing the enzymes (1,3) glucanase and chitinase that cause exolysis of the host hyphae [14]. Trichoderma enzymes could degrade the cell walls of the pathogenic fungus [24].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the analyses indicated that the colony diameter of the pathogen in the control sample was 82.66 mm, while in the bicultures, the diameters of A. solani were 30.6 mm, 27.3 mm, and 23.3 mm for T. atroviride, T. harzianum, and T. longibrachiatum, respectively. Sudantha and Suwardji [110] proved that T. hamatum, T. harzianum, T. koningii, T. longibrachiatum, T. piluliferum, and T. viride reduced the growth of F. oxysporum on a PDA medium by an average of 64.8-77.2%. In turn, Modrzewska et al [111] reported that T. atroviride, T. viride, and T. viridescens inhibited the development of F. cerealis and F. culmorum by 24-66%.…”
Section: Competition For Nutrients and Spacementioning
confidence: 99%
“…Microscopic observation of the contact area of B. theobromae and antagonistic fungi in figure 4 showed that cell lysis occurred in B. theobromae hyphae. The competition mechanism occurs when antagonistic fungal colonies cover pathogenic colonies and the growth of antagonistic fungi is faster to fill the petri dish and in the contact area, pathogenic hyphae underwent lysis [12]. Aspergillus sp.…”
Section: Aspmentioning
confidence: 99%
“…The initial growth of the Trichoderma sp. mycelia elongates, then entangles and penetrates the host fungal hyphae untill vacuolization, lysis and finally disintegrates [12]. Furthermore, these antagonists grow and coil in the pathogenic hyphae to inhibit the pathogen's spread [9,21].…”
Section: Aspmentioning
confidence: 99%